“The Effect of Repeated Television Advertisement Message of Mastin Towards Its Consumer Buying Decision through Brand Image” - NARENDRA LAKSONO MAHASIN (Jurnal Ilmiah Mahasiswa FEB, 2017)
A company must be able to advertise their products in every single way. Along with the revolution of technology, advertisement can be done in several ways. One way is a television advertisement.There are also several types of television advertisement. Repetitive advertisement is one of the examples. One famous advertisement that uses this method is the television advertisement of Mastin. The advertisement looks cheap by only having a simple graphic that is repeated three times. Hypothetically speaking, an advertisement of this type should draw viewers’ attention and implant itself in the minds of a consumer. Keywords: Advertisement, Television Advertisement, Repeated Advertisement